2005
DOI: 10.1002/psc.635
|View full text |Cite
|
Sign up to set email alerts
|

Solid phase synthesis of anthraquinone peptides and their evaluation as topoisomerase I inhibitors

Abstract: Anthraquinone peptide derivatives have previously been shown to inhibit the enzyme topoisomerase I (topo I), a pharmaceutical target for the prevention of malignant carcinomas. A highly efficient procedure for the attachment of the anthraquinone moiety to the N-terminus of a peptide on a solid support is reported. This methodology provides a convenient method for the synthesis of labelled peptides, with potential applications for chemotherapy, DNA detection and protein purification. As the synthetic strategy u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Previous studies showed that peptide−anthraquinone analogues inhibit the catalytic activity of DNA topoisomerase I and stabilize the so-called “cleavable complexes” between DNA and the enzyme . Therefore, we determined if drug−tuftsin conjugates exert a similar effect on the activity of purified types I and II DNA topoisomerases.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies showed that peptide−anthraquinone analogues inhibit the catalytic activity of DNA topoisomerase I and stabilize the so-called “cleavable complexes” between DNA and the enzyme . Therefore, we determined if drug−tuftsin conjugates exert a similar effect on the activity of purified types I and II DNA topoisomerases.…”
Section: Resultsmentioning
confidence: 98%
“…The condensation between leuco-1,4-dihydroxy-9,10-anthraquinone ( 1 ) and the N-termini of the peptide−resin ( 2 ) was achieved during reaction in N , N- dimethylformamide (DMF) at 120 °C under N 2 for 24 h. A 3-fold excess of leucoanthraquinone was used in the reaction. Then peptidyl-anthraquinone-resin was oxidized by air oxygen at room temperature. , To cleave the product from resin with simultaneous removal of all the side chain protecting groups, dried peptidyl-anthraquinone-resin was treated with a mixture of trifluoroacetic acid (TFA), triisopropylsilane (TIS), and water. The tuftsin conjugates were purified by solid-phase extraction (SPE) and preparative HPLC (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[36] On the other hand, leucoquinizarin's peptides have been recently reported to afford topoisomerase I inhibition. [37] The chelation process of these hydroxyanthraquinones usually evolves via their tautomeric anthraquinoid structures. [38] The formation of a wide variety of metal complexes has been reported for quinizarin and anthrarufin, [39] while alizarin exhibiting linkage isomerism, acts as a chelate via the 1,2-or the 1,9-oxygen atoms and forms complexes with Ru, Cu, Ni, Hg, and a variety of transition metals.…”
Section: Introductionmentioning
confidence: 99%